Chronic diarrhea in under 2 year aged children, a ten year retrospective analysis - Arif, Hala S.; hamody, karim (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Diarrheal diseases are still a major public health problem especially in developing countries, due to their high morbidity & mortality rates, moreover the lagest number of deaths with diarrheal diseases are due to persistent diarrheal states.We attemted to evaluate the size of the problem in our infants, and assess risk factors & outcome. Methods: A retrospective study was performed in Al-Kadhemya teaching hospital, to evaluate diarrheal cases in under 2 years of age children , admitted to hospital during the period (Dec. 1991- Dec. 2001), from a total of 863, chronic diarrheal cases formed 286 (33.14%) that were evaluated for certain variables; epidemiology & risk factors etiology ,complications and the final outcome . Results & Conclusion:We concluded that: chronic diarrhea formed more than 33% of admitted diarrheal cases to the hospital, of the important risk factors for diarrhea both acute & chronic types were bottle feeding , young age. Lactose intolerance,parasitic infestations and UTI were the common etiologies. Malnutrition was common in cases of chronic diarrhea together with multiple clincal and lab derrangements.The mortality rate was -4%. Abreviations: CNS: central nervous system, GFD:gluten free diet, Hb: hemoglobin, ORT: oral rehydration therapy, PD: protracted diarrhea, PCM:protein-calori malnutrition,UTI: urinary tract infection.